JAKOŚĆ W MEDYCYNIEReturn to life and the quality of life assessment after hart transplantation - Jaworska, Izabela; Pudlo, Robert; Pacholewicz, Jerzy; Szyguła-Jurkiewicz, Bożena; Barańska-Kosakowska, Anna; Dylewska, Aleksandra; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
On 5 th November 1985 Zbigniew Religa performed the first successful Polish heart transplantation. We have been performing the heart transplantation to save the patient with end-stage heart failure for 25 years now in Silesian Center for Heart Disease in Zabrze. These operations improve the patients’ life comfort and allow them to lead the lifestyle which is similar to the one led by healthy people. The recipients’ quality of life may be influenced by factors such as: the necessity of regular check-up visits, taking medicine, the ability of coping with stress, personality features and the presence of anxiety and mood disorders. Because of these factors the team looking after the patients who have undergone a heart transplantation should also include a psychiatrist and a psychologist